Nærlys på tvang og makt overfor personer med utviklingshemming - Margunn Rommetveit; Anita Tollefsen (Septentrio Academic Publishing, 2015)
Focusing at the use of coercion and force against people with intellectual disability The use of coercion and force against people with intellectual disability has been regulated by law in Norway since 1999. Each episode of coercion is challenging the human rights and has the potential to be an act of violation. The requirements for proceedings, ethical considerations and the requirements for professional competences, is special in Norway comparing to the other Scandinavian Countries. The article examines the notifications of coercion and the claim form from the staff working in communities with people with intellectual disability. The notifications of coercion have different approach. The attitude and the way of behavior are strongly related to the approach. The language in the notifications is strongly different. We talk about a subject-subject-relation and a subject-object-relation. It seems like there can be less use of coercion and force, if the staff involved, has the knowledge of how important the relation affect on the good interaction. The staffs own role, in preventing the need of using coercion and force, can be better recognized and improved.